2022
DOI: 10.1007/s12265-022-10342-w
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extracellular Vesicles on Thrombosis

Abstract: The risk of cardiovascular events caused by acute thrombosis is high, including acute myocardial infarction, acute stroke, acute pulmonary embolism, and deep vein thrombosis. In this review, we summarize the roles of extracellular vesicles of different cellular origins in various cardiovascular events associated with acute thrombosis, as described in the current literature, to facilitate the future development of a precise therapy for thrombosis caused by such vesicles. We hope that our review will indicate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 148 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have documented that EVs released by cancer cells could promote a pro-coagulant shift on endothelium, which expresses Tissue Factor (TF) and thrombin. Moreover, it has been demonstrated that cancer cells release TF-enriched EVs, which activate platelets and favor their aggregation [ 48 ]. Lastly, we must report that the thrombotic risk of chemotherapy and other cancer treatments has still to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented that EVs released by cancer cells could promote a pro-coagulant shift on endothelium, which expresses Tissue Factor (TF) and thrombin. Moreover, it has been demonstrated that cancer cells release TF-enriched EVs, which activate platelets and favor their aggregation [ 48 ]. Lastly, we must report that the thrombotic risk of chemotherapy and other cancer treatments has still to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Their abundance in the bloodstream and pivotal roles in processes such as wound healing, angiogenesis, thrombosis, and atherosclerosis make them a significant focus of study [ 201 , 202 , 203 , 204 ]. The isolation of these EVs, which requires further study, could aid the understanding and treatment of a variety of clotting disorders and thrombocytopenias [ 205 ]. Red blood cell-derived EVs (RBC-EVs) have also attracted attention due to their potential role in erythropoiesis, iron homeostasis, and hemolysis.…”
Section: Cts-evs In Physiology and Pathologymentioning
confidence: 99%
“…Recent technological advances, particularly in electron microscopy, have supported growing interest in extracellular vesicles (EVs), small cell-derived particles whose role extends beyond intercellular communication. These lipid bilayer structures play a critical role in physiological and pathological processes, including immune response, cancer metastasis [ 80 ], endothelial dysfunction and thrombosis [ 81 ]. Extracellular vesicles, which are classified according to their size, density and centrifugation speed [ 82 , 83 , 84 ], are divided into three main types.…”
Section: Role Of Extracellular Vesicles In Thrombosismentioning
confidence: 99%
“…The release of EVs is not restricted to specific cell types, and surface antigens reflect their cellular origin, facilitating detection by flow cytometry. The surface markers for different EVs according to their origin are listed in Table 2 [ 81 , 89 , 90 ]. Platelet-derived EVs are the most common, followed by those from endothelial cells, granulocytes and erythrocytes [ 91 , 92 ].…”
Section: Role Of Extracellular Vesicles In Thrombosismentioning
confidence: 99%